Why Islamic Banks are Relatively More Resilient to Crisis? - Hasna Maliha; Lina Marlina (SMART Insight, 2019)
The financial crisis repeatedly struck various countries in the world in rotation, both developing and developed countries. In fact, in the modern economic period like now, the intensity is becoming more frequent and acute. Therefore, an early crisis detection system becomes important to avoid the more severe negative impact of the crisis. This study tries to examine what indicators can be used as a reference in predicting how likely there will be a crisis in a dual banking country such as Indonesia by using the binary logistic regression method. The results show interesting important conclusions. First, Islamic banks tend to have problems with liquidity (with significant FAR evidence) while conventional banks tend to have problems with solvency (significant CAR). From this, it follows that the Islamic bank will only be in crisis if the real sector is disrupted. While conventional banks will always flare up if there is a disruption of the financial crisis. Second, related to the significant M2RES variable, both in the Islamic and conventional models, this could be a result of the enactment of fiat money and fractional reserve banking system (FRBS). Though both of these are contributors to excess money supply which is quite large. So it becomes reasonable to understand if both models - both Islamic and conventional - have similar conditions. As a consequence, the Islamic banking entity is not going to be free from the adverse effects of the financial crisis. The third conclusion that is no less important is departing from the fact that the interest rate (INTR) turns out to be significant in the conventional model but not if it is in the sharia model, it can be concluded that a policy rate such as the BI-rate is very effective at controlling and influencing instruments Other monetary policies follow also the behavior of conventional banks. But on the other hand, this also indicates that conventional banking is indeed quite vulnerable to monetary shocks and financial crises. Thus, it becomes a rational reason for monetary authorities, in this case, Bank Indonesia to provide more support to the sustainability of Islamic finance and banking in Indonesia to achieve stable and optimal monetary conditions.